PENGARUH PEMBERIAN MATA KULIAH KEWIRAUSAHAAN TERHADAP MINAT MAHASISWA BERWIRAUSAHA - Sitompul, Pandapotan; Silalahi, Donalson; Munthe, Kornel; Nauli, Kembang; Sinambela, Julivacius Gok Asi (LPPM Universitas Katolik Santo Thomas Medan, 2024)
The purpose of this study was to determine and explain the effect of providing entrepreneurship courses on students' interest in entrepreneurship. Data collection was carried out using a questionnaire. Before the hypothesis test was carried out, a classical assumption test was carried out first. The analysis used simple linear regression, t-test hypothesis testing and determination coefficient analysis. From the results of data processing, a simple linear regression equation was obtained where: Y = 7.616 + 0.457 X + ei. The results of this study indicate that 1) There is an effect of providing entrepreneurship courses on students' interest in entrepreneurship, this is indicated by the calculated t value > t table (2.058 > 1.985); 2) There is a moderate relationship between providing entrepreneurship courses and students' interest in entrepreneurship because the correlation coefficient value is 0.479 which lies between 0.40 - 0.599; 3) The percentage contribution of the influence of the independent variable (providing entrepreneurship courses) to the dependent variable (students' interest in entrepreneurship) is 22.9%. Or the variation of independent variables used in the model (giving entrepreneurship courses) is able to explain 22.9% of the variation of the dependent variable (students' interest in entrepreneurship). While the remaining 77.1% is influenced or explained by other variables not included in this research model.